Visible Light‐Mediated Conversion of Alcohols to Bromides by a Benzothiadiazole‐Containing Organic Photocatalyst. Issue 16 (5th July 2019) - Li, Run; Gehrig, Dominik W.; Ramanan, Charusheela; Blom, Paul W. M.; Kohl, Fabien F.; Wagner, Manfred; Landfester, Katharina; Zhang, Kai A. I.
Abstract: The search for metal‐free, stable and high effective photocatalysts with sufficient photo‐redox potentials remains a key challenge for organic chemists. Here, we present a benzothiadiazole‐containing molecular organic photocatalyst with redox potentials of −1.30 V and +1.64 V vs . SCE. The singlet state lifetime is 13 ns. Direct conversion from aliphatic alcohols to bromides has been conducted with the designed organic photocatalyst under visible light irradiation with high efficiency and selectivity. The catalytic efficiency of the novel benzothiadiazole‐based photocatalyst is comparable with the state‐of‐art metal and non‐metal catalysts. Furthermore, advanced photophysical studies including time‐resolved photoluminescence and transient absorption spectroscopy offer a powerful support for photo‐induced electron transfer from photocatalyst to the reactive substrates. Lastly, no photo‐bleaching effect is observed, demonstrating the high stability and recyclable of the designed organic photocatalyst. Abstract :